Implementation of Communicative Method as an Effort to Increase the Student’s Arabic Language Ability (Case Study at SDI Surya Buana Malang) - Minatullah Minatullah; Ahmad Fatoni; Anisatu Thoyyibah (Maharaat: Jurnal Pendidikan Bahasa Arab, 2019)
The purpose of this study was to determine the results of the communicative method in improving the ability of mahârah al-kalâm, barriers to its implementation, and how to overcome communication barriers to the students at SDI Surya Buana Malang class VA for one semester in the 2018/2019 academic year. This research employed qualitative methods by taking field data or case study research. The data was collected by using observation, interview, and documentation techniques. The result of the research showed that there was no improvement in students' mahârah al-kalâm through the application of the communicative method. Students could only use short sentences in Arabic that had been memorized. The obstacle during the implementation of the communicative method was that the students were not fluent in reading iqra’ which resulted in the hardship of reading Arabic. Lack of Arabic lessons in schools caused inadequate Arabic learning process and students' lack of memorization of mufradât caused some difficulties in learning sessions. An effort to overcome these obstacles was that the teacher must provide extra sessions for students who could not read iqra’ fluently. Schools must also give extra sessions for Arabic lessons, and the teacher instructed all students to memorize vocabulary in accordance to the theme of the lesson.